Usages et limites de la violence de guerre à la haute époque hellénistique - Isabelle Pimouguet-Pédarros (Kentron)
Does war violence, which is widely considered as a category intrinsically linked to the military, or even as one of its components, have its own specificities in the Hellenistic period? Did the historical and cultural representations of war violence evolve in relation to earlier periods? Did the ongoing struggles and rivalries between the various Greek powers for command of conquered territories lead to a shift in tolerance thresholds? Considering that war violence differs from one space of time to another, this study aims to characterize and identify with precision the acts that fall within its scope, as well as to highlight the way in which these acts are reported by ancient authors and integrated into the narrative of events. But beyond the forms and representations of war violence, this study also aims to account for acts that fall within the scope of transgression – whether in violation of fundamental norms or disregard of custom. The aim is therefore not only to consider the situations in which these acts occur, but also to highlight the vocabulary associated with them, likely to reflect the crossing of a moral boundary, or even an infringement of the rules governing man’s relationship with the divine. From this point of view, Polybios’ writings are particularly interesting in that they raise the question of a possible redefinition of the uses and limits of war violence in the Hellenistic period.